2020
DOI: 10.1016/j.yebeh.2020.107121
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating psychogenic nonepileptic from epileptic seizures: A mixed-methods, content analysis study

Abstract: Background: Identification of clinical features that might distinguish psychogenic nonepileptic seizures (PNES) from epileptic seizures (ES) is of value for diagnosis, management, and understanding of both conditions. Previous studies have shown that patients' descriptions of their seizures reflect differences in content and delivery. We aimed to compare verbal descriptions of PNES and ES using a mixed-methods approach. Methods: We analyzed data from semi-structured interviews in which patients with video-elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although the pathophysiology of PNEEs is still poorly understood compared to epilepsy, the increased respiratory rate or hyperpnea during and after PNEEs has been reported 24–26 . This activated respiratory pattern has also been used in previous studies to differentiate PNEEs from epilepsy 27,28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathophysiology of PNEEs is still poorly understood compared to epilepsy, the increased respiratory rate or hyperpnea during and after PNEEs has been reported 24–26 . This activated respiratory pattern has also been used in previous studies to differentiate PNEEs from epilepsy 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] This activated respiratory pattern has also been used in previous studies to differentiate PNEEs from epilepsy. 27,28 The concentration of several ions was also ranked as important features of the random forest model, including calcium, chloride, and potassium. This may be related to the mechanisms in epileptogenesis of dysfunction of structures responsible for maintaining ionic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer reports of ictal self-injury and post-seizure aches and amnesia may also favors the possibility of PNES. [23] Risk factors:…”
Section: Speci C Objectivesmentioning
confidence: 99%
“…However, many of these medications can cause adverse effects for patients (6) and impose costs on patients, communities, and healthcare systems (7). Therefore, finding accurate and available ways to diagnose and differentiate these two disorders can help specialists determine the etiology and dynamics of both disorders (10).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also reported better cognitive performance in PNES, while others have reported worse cognitive performance in comparison with ES (13,14). Neuropsychological assessments can provide clues for the differential diagnosis of PNES and ES and help clarify their nature and etiology (6,10).…”
Section: Introductionmentioning
confidence: 99%